Exploring Synergy in Combinations of Tumor-Derived Vaccines That Harbor 4-1BBL, OX40L, and GM-CSF - Manrique-Rincón, Andrea J.; Beraldo, Camila M.; Toscaro, Jessica M.; Bajgelman, Marcio C. (Frontiers in Immunology, 2017)
Recent studies have demonstrated that combination of modulatory immune strategies may potentiate tumor cell elimination. Most strategies rely on the use of monoclonal antibodies that can block cell surface receptors to overcome tumor induced immunosuppression or acting as costimulatory ligands to boost activation of T cells. In this study, we evaluate the use of combinations of genetically modified tumor-derived cell lines that harbor the costimulatory T cell ligands 4-1BBL, OX40L and the cytokine GM-CSF. The aim of these treatments is to boost the activation of T cells and the elimination of cancer cells. These tumor-derived cells are able to activate or reinforce T cell activation, thereby generating a potent and specific antitumor response. We developed a high-content in vitro imaging assay that allowed us to investigate synergies between different tumor-derived cells expressing modulatory immune molecules, as well as the influence on effector T cells to achieve tumor cell death. These results were then compared to the results of in vivo experiments in which we challenged immunocompetent animals using the B16F10 syngeneic model of melanoma in C57BL6 mice. Our results suggest that there is a substantial therapeutic benefit to using combinations of syngeneic tumor vaccines that express immune modulators. In addition, we observed that combinations of tumor-derived cells that expressed costimulatory ligands and GM-CSF induced a long-term protective effect by preventing cancer development in both cured and re-challenged animals.